2017
DOI: 10.1002/ep.12533
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid approach based on cuckoo search optimization algorithm for short‐term wind speed forecasting

Abstract: A type of renewable energy, wind power, which has a large generating capacity, has increasingly captured the world's attention. Forecasting wind speed is of great significance in wind‐related engineering studies, the planning and designing of wind packs, wind farm management and the integration of wind power into electricity grids. Because of the chaotic nature and intrinsic complexity of wind speed, reducing forecasting errors related to wind speed has been an important research subject. This article proposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In Refs. [10,19,27,46] and [60], the IMFs were categorized into two bands with high and low frequency components. These articles stated the IMFs with lower frequency bands represent the central tendency of the data and highly regular pattern which shows the accurate characteristics of the original data, whereas the IMFs with higher frequencies contain large quantity of noisy signals, which mainly reflects the random information that led to a great disturbance for prediction precision of wind data.…”
Section: Intrinsic Mode Functionsmentioning
confidence: 99%
“…In Refs. [10,19,27,46] and [60], the IMFs were categorized into two bands with high and low frequency components. These articles stated the IMFs with lower frequency bands represent the central tendency of the data and highly regular pattern which shows the accurate characteristics of the original data, whereas the IMFs with higher frequencies contain large quantity of noisy signals, which mainly reflects the random information that led to a great disturbance for prediction precision of wind data.…”
Section: Intrinsic Mode Functionsmentioning
confidence: 99%
“…Investigators have implemented many different methods to ameliorate the forecasted energy of wind speed . The short‐term prediction showed a high accuracy rate compared with other steady predictions . The price management in markets by improving daily‐ahead market (DM) and fulfilling markets bidding in adjusted market (AM) is one of the methods suggested for increasing market‐rate profits.…”
Section: Introductionmentioning
confidence: 99%
“…2 The short-term prediction showed a high accuracy rate compared with other steady predictions. 3 The price management in markets by improving daily-ahead market (DM) and fulfilling markets bidding in adjusted market (AM) is one of the methods suggested for increasing market-rate profits. Afshar et al4 presents a compound energy to the markets, aiming to encourage the generators of a natural resource to adapt their generated power to market prices.…”
Section: Introductionmentioning
confidence: 99%
“…Yang proposed a BP neural network image restoration algorithm optimized by Gray Wolf algorithm, whose results showed that the algorithm had faster convergence speed and higher restoration accuracy than the Genetic Algorithm-Back Propagation (GA-BP) algorithm [15].Considering the high complexity and volatility of the icing thickness, most historical literature directly model and predict the icing thickness, so the effect is not ideal. Therefore, this paper uses Ensemble Empirical Mode Decomposition (EEMD) method for the first time to decompose the icing thickness, which effectively solves the problem of mode aliasing, retains the real signal to the maximum extent, builds the prediction model based on the decomposition of the original signal, and can effectively improve the accuracy [16][17][18][19][20][21][22].From another perspective, as transmission line icing thickness is a time series change, two prediction methods were proposed to predict accuracy icing thickness data. One is based on historical data of icing thickness, but as the phenomenon of ice coating on the transmission line is a physical phenomenon determined by various factors, the prediction of this method is not accurate.…”
mentioning
confidence: 99%
“…Considering the high complexity and volatility of the icing thickness, most historical literature directly model and predict the icing thickness, so the effect is not ideal. Therefore, this paper uses Ensemble Empirical Mode Decomposition (EEMD) method for the first time to decompose the icing thickness, which effectively solves the problem of mode aliasing, retains the real signal to the maximum extent, builds the prediction model based on the decomposition of the original signal, and can effectively improve the accuracy [16][17][18][19][20][21][22].…”
mentioning
confidence: 99%